Lingual frenulum phenotypes in Brazilian infants with congenital zika syndrome - Fonteles, Cristiane Sá Roriz; Marques Ribeiro, Erlane; Sales Aragão Santos, Marinisi; Ferreira Pequeno Leite, Rebeka; Sales Assunção, Gabryela; Monteiro, André Jalles; Santos Pessoa, André Luiz; Giacheti, Célia Maria [UNESP]; Cavalcante Kerbage, Sáile; Ribeiro, Thyciana Rodrigues; Pamplona de Goés Cavalcanti, Luciano (SAGE Publications, 2018)
Objective: The present study aimed to evaluate lingual frenulum in children affected by congenital Zika syndrome (CZS) and to analyze the association of lingual frenulum phenotypes with other variables. Design: This present work had a cross-sectional, descriptive study design. Setting: This study was carried out in Fortaleza (Brazil). The health professionals provided tertiary level of care. Data collection occurred during a multidisciplinary task force for evaluating infants affected by CZS in December 2 to 3, 2016. Patients: Fifty-four patients with CZS (1-12 months old; 32 girls and 22 boys) were recruited from a population of 70 infants. Interventions: A multidisciplinary group comprised of speech-language pathologist/audiologists and pediatric dentists evaluated all patients through an intraoral examination and a specific tongue maneuver protocol for infants. Main Outcome Measures: Lingual frenulum visibility was the primary outcome measure. Before initiating the study, we hypothesized that children with CZS had an absent lingual frenulum. Results: Lingual frenula were visible in 34 (63%) infants, whereas in 20 (37%) infants lingual frenula visibility required a specific maneuver to retract the tongue. Six of 20 infants presented posteriorly positioned lingual frenula that were visible after maneuver. Lingual frenula were covered by mucous tissue in 14 infants. Presence of posterior frenulum was associated with dysphagia (P = 0.038). However, the presence of dysphagia in a multivariate model did not associate with the presence of a posterior lingual frenulum (P =.069) or neurologic symptoms (P =.056). Conclusion: Children with CZS showed predominance of a posterior lingual frenula covered by an overlapping curtain-like mucous membrane.
Keywords: Lingual frenum; Microcephaly; Stomatognathic system; Zika virus